Percepção de adictos sobre a qualidade de vida e a inserção de atividade física orientada em comunidades terapêuticas de Campo Grande, MS - Cosmo, Raphael de Souza (2022)
Theme: Addicts' perception of quality of life and the insertion of guided physical activity in therapeutic communities in Campo Grande, MS; such an approach emphasizes chemical dependence as a chronic disease that has several causes, whether physiological, behavioral or cognitive, and the use of psychoactive substances causes damage to users and interferes with quality of life, in most cases. Justification: Physical activity collaborates in the treatment plan for addicts, as it presents an option to feel good without using drugs; and with the care of professionals who are prepared and welcome in a new way of life, it can cooperate for these subjects to regain their self-esteem, restart their social life in a healthier way, so the insertion of oriented physical activity can collaborate in the treatment plan and in the quality of life, in the perception of addicts residing in therapeutic communities in Campo Grande, Mato Grosso do Sul, justified this study. Objective: the objective of this study was to evaluate the perception of addicts about the insertion of guided physical activity, the quality of life and the insertion of guided physical activity in therapeutic communities in Campo Grande, MS. Method: Case study, observational cross-sectional characterized qualitative and quantitative, of an applied nature with field procedures to addicts participating in six therapeutic communities in Campo Grande -MS; at least 5% of participating addicts were required, and to compensate for possible losses and refusals, an addition of 10 to 15% was made. Two questionnaires were applied: a) Physical activity - through a semi-structured questionnaire (Appendix C); b) Quality of life through the WHOQOL-bref – quality of life assessment (Appendix D). Results: The research is relevant, as it exposes issues relevant to the recovery of addicts through oriented physical activity and aiming to make them aware of this practice as an ally in the recovery plan. Younger addicts (18 to 30 years old) reported greater involvement in regular physical activity in the TC (90.2%) compared to older addicts (over 30 years old), as well as addicts with less time of hospitalization (less than 6 months) is more physically active (76.45%), than the addicts with longer hospitalized (over 6 months), with (59.5%). Addicts with a spouse have a greater social environment (70.3%) than those who do not have a spouse (52.1). Regarding the environment where the addicts are inserted, those who are in public administration (61.5) judged it negative, against (45.6) who are in private administration. Conclusion: the insertion of guided physical activity and the perception of quality of life and satisfaction with health through the physical, psychological, social relationships and environments of addicts residing in therapeutic communities in Campo Grande/MS, it is necessary to disclose the importance of physical education professionals in the context of drug addiction treatment, inserting physical exercise programs into therapeutic strategies to accelerate the recovery process and offering addicts physiological support to prevent relapses and improve health and quality of life .